Comparison of specimen-specific vertebral body finite element models with experimental digital image correlation measurements. (January 2017) - Gustafson, Hannah M.; Cripton, Peter A.; Ferguson, Stephen J.; Helgason, Benedikt
Abstract: The purpose of this study was to load cadaveric vertebral bodies (n=6) in compression and compare the response, measured with digital image correlation (DIC) on the cortex, with the predicted response from specimen-specific vertebral finite element (FE) models. Five modulus-density relationships were evaluated, and for the strongest modulus-density relationship, the correlation between the DIC and FE displacements had R 2 values from 0.75 to 0.93. The stiffnesses derived from the DIC measurements were strongly predicted by the FE stiffnesses (R 2 =0.90). DIC provides full-field measurements of surface displacement, eliminating the influence of system compliance, for validation of specimen-specific models.